Sobre as utilidades do cadastro único - Ricardo Paes de Barros; Mirela de Carvalho; Rosane Mendonça (Instituto de Pesquisa Econômica Aplicada (IPEA), 2009)
– The goal of the Cadastro Único para Programas Sociais (CadÚnico) is the registration and maintenance of updated information of all Brazilian families with per capita income less than R 120.00. Although the use of CadÚnico continues focusing on the selection of beneficiaries of the Bolsa Família, there is a wide range of uses that incipiently or already has been adopted, or that could be employed in the future. Three features of CadÚnico define their scope of use. First, its scope is almost a census, covering almost the entire poorest population of the Country. Secondly, because of its nature, the CadÚnico includes the name and address of the poor population. Finally, although the selection of beneficiaries of the Bolsa Família program use only the information of income, the CadÚnico contains a wide variety of information about the living conditions of these families that can be used for a diagnosis and shaping of the Country social policy. The objective of this work is to demonstrate that the variety of information available on families and the possibility to identify these families, leads to that Cad Único had many uses. More specifically, we demonstrate how this information can be used in the preparation of diagnoses on the living conditions of families, municipalities, states and even the Country as a whole.
Keywords: I38; 330